The Impact of Pandemic on Bancakan Salak Cultural Tourism - Firdaus, Praja; Suksmawati, Herlina; Hapsari, Renitha; Kusuma, Ade (Journal of Indonesian Tourism and Development Studies, 2022)
This second-term research examined the dynamics of Bancakan Salak cultural tourism after being hit by the COVID-19 pandemic. Knowing how the tourism strategy was implemented in the times of pandemic and what were the tips to be able to survive in this limited condition were two interesting things this article studied. Like many other tourist attractions, Bancakan Salak cultural tourism was also affected by the pandemic. Yet, as previous research has concluded, Galengdowo's local society had three essential traditional values reflected in Bancakan Salak cultural tourism that helped them to get through this situation. These three values were collectivism, gratitude, and almsgiving. These three values also created further key concepts in responding to the pandemic, the importance of resilience, and innovation. Using qualitative method (in-depth interview) combined with the observation participatory method, and also ABCD (asset-based community development), this article highlighted the crucial role of human basic needs resilience and socio-cultural resilience. Because in the era of globalization nowadays, connectivity had proven could be substituted by collectivism, gratitude, almsgiving, and other traditional values that hold tight the element of togetherness. This article also highlighted the role played by cultural assets and personal assets to build villages' capacity. In the end, Bancakan Salak and its tourism industry in Galengdowo was hit by the pandemic and Galengdowo's local society responded with resilience and innovation.   Keywords: Bancakan Salak, cultural tourism, community, pandemic, globalization.